Influence of food processing operations on vitamins - Tomaş, Merve; Jafari, S.M. (Elsevier, 2018)
Considering the increasing demand of consumers for nutritious and functional foods, manufacturers in the food industry have to develop preservation technologies to ensure that the nutrients of the foods are lost to a minimum. Vitamins are bioactive compounds which are important to human health. Since vitamins are sensitive to degradation, food processing operations can have either negative or positive effects on them. This review provides an overview of what is currently known about the effects of food processing operations on vitamins. The influence of conventional and modern food processes on different vitamins has been covered in this chapter. © 2019 Elsevier Inc.
Keywords: Non-thermal processing; Processing effects; Thermal processing; Vitamins